Citra Perempuan dalam Cerpen Sambal di Ranjang Karya Tenni Purwanti: Kajian Feminisme - Kanthi Wilujeng; Een Nurhasanah; Slamet Triyadi (Universitas Ngudi Waluyo, 2021)
This paper aim to describe:1) Form of gender injustice to female characters in Sambal & Ranjang short story by Tenni Purwanti, 2) To describe the image of woman in the Sambal di Ranjang short story by Tenni Purwanti by using a feminist literary criticism approach. The research is a qualitative study using descriptive methods. Sources of data in this paper is the short story contained in the book of Sambal & Ranjang by Tenni Purwanti, published by Gramedia Pustaka Utama, Jakarta, first edition, October 2020. Instrument research is the researcher himself because the researcher as data collector and also as data analyzer. The conclusion of this study is the physical, psychological, and social image of the main female characters in the Sambal di Ranjang short story by Tenni Purwanti showing a view of woman.